Implementing the Baby One Program: a qualitative evaluation of family-centred child health promotion in remote Australian Aboriginal communities - Sandra Campbell; Janya McCalman; Michelle Redman-MacLaren; Karla Canuto; Kristina Vine; Jenny Sewter; Malcolm McDonald (BMC, 2018)
Abstract Background A healthy start predicts better health in later life. Many remote-living Aboriginal and Torres Strait Islander Australian families lack access to consistent, culturally-safe health services. This paper presents a study of implementation of the Baby One Program (BOP). The BOP was designed as a family-centred, Indigenous Healthworker-led, home-visiting model of care focused on promoting family health to give children the best start to life. It was developed by Aboriginal community-controlled Apunipima Cape York Health Council and delivered in Queensland Cape York remote communities. We aimed to determine how the BOP was implemented, enablers, strategies used and formative implementation outcomes. Methods The qualitative approach utilised theoretical and purposive sampling to explore people's experiences of a program implementation process. Data were generated from semi-structured interviews with four family members enrolled in the BOP and 24 Apunipima staff members. In addition, twenty community members, including two program users, participated in a men's community focus group. The findings are presented according to themes arising from the data. Results The BOP was rolled out in nine remote Cape York communities between July 2014 and December 2015 and there was high uptake. Indigenous Healthworkers were supported by midwives and maternal and child health nurses to deliver health education to 161 eligible families. The key to effective implementation of family-centred care appeared to be the relationships formed between health practitioners, especially Indigenous Healthworkers, and families. The data revealed the following themes: challenging environments for new families and valuing cultural ways, resourcing program delivery, working towards a team approach, negotiating the cultural interface, engaging families, exchanging knowledge through 'yarning', strengthening the workforce, and seeing health changes in families. Healthworker education and training, and knowledge exchange between Healthworkers, midwives and nurses was critical to program effectiveness. The program continues to grow despite substantial logistic, financial and practical challenges. Conclusions This study describes an evolving process and explores how health providers connect with families and how the program responds to family and cultural issues. Program development is ongoing; strengthened by more community-level involvement, embedded strategies for ongoing self-evaluation and continuous quality improvements that are responsive to family needs.